Study on dynamic stability for the superlong pile foundation of marine engineering structures in service. (July 2022) - Gu, Wenyin; Yao, Wenjuan; Shi, Yusha; Xie, Liquan; Lian, Xuebiao; Zhou, Jian; Wen, Xuejun
Abstract: To fully utilize the earth's resources, the offshore structure is a growing trend for human development. Pile foundations are widely used to support offshore structures. In the ocean, wave loads and ship impacts (SIs) may cause the instability or failure of the pile-soil system. This paper studies the dynamic stability of the pile foundation of offshore structures under both wave loads and SIs. The two-parameter foundation model and Galerkin integral method are used to establish offshore structures' nonlinear dynamic differential control equations. The displacement function of the pile body is obtained by using the fourth-order Runge-Kutta method, and the instability load of the pile body is obtained from the displacement time-history curve. The influence of pile length, stiffness, and soil properties on pile performance is investigated. Through the study of this paper, it can be found that the constraint effect of the soil on the side of the pile can make the pile experience a period of steady-state vibration before the instability; that is, the instability of the pile is delayed. Compared with the traditional Winkler model, the instability load and displacement time history curve calculated by the two-parameter model are more in line with the engineering practice.